Serine Protease Activation Essential for Endothelial-Mesenchymal Transition in Vascular Calcification - Yao, Jiayi (Circ Res, 2015)
RATIONALE: Endothelial cells have the ability to undergo endothelial-mesenchymal transitions (EndMTs), by which they acquire a mesenchymal phenotype and stem-cell like characteristics. We previously found that EndMTs ocurred in the endothelium deficient in matrix Gla protein (MGP) enabling endothelial cells to contribute cells to vascular calcification. However, the mechanism responsible for initiating EndMTs is not fully understood. OBJECTIVE: To determine the role of specific serine proteases and sex determining region Y-box 2 (Sox2) in the initiation of EndMTs. METHODS AND RESULTS: In this study, we used in vivo and in vitro models of vascular calcification to demonstrate that serine proteases and Sox2 are essential for the initiation of EndMTs in MGP-deficient endothelium. We showed that expression of a group of specific serine proteases was highly induced in endothelial cells at sites of vascular calcification in Mgp null aortas. Treatment with serine protease inhibitors decreased both stem-cell marker expression and vascular calcification. In human aortic endothelial cells, this group of serine proteases also induced EndMTs, and the activation of proteases was mediated by Sox2. Knockdown of the serine proteases or Sox2 diminished EndMTs and calcification. Endothelial-specific deletion of Sox2 decreased expression of stem-cell markers and aortic calcification in MGP-deficient mice. CONCLUSIONS: Our results suggest that Sox2-mediated activation of specific serine proteases is essential for initiating EndMTs, and thus, may provide new therapeutic targets for treating vascular calcification.